2020
DOI: 10.21708/avb.2020.14.2.8772
|View full text |Cite
|
Sign up to set email alerts
|

Intestine vascularization of sloth (Bradypus variegatus SCHINZ, 1825)

Abstract: Article historyCommon sloth (Bradypus variegatus) is a mammal that belongs to the superorder Xenarthra, typical from neotropical regions, with geographic distribution from Honduras to northern Argentina. Our study aimed to describe the intestine blood supply of these Bradipodids in order to collaborate with the clinical-surgical for these animals. For that, ten animals, included four females and six males, were sampled from the collection of the Anatomy Division,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…Souza et al (2010) found that the large intestine (colon and rectum) of the giant anteater ( Myrmecophaga tridactyla ) is vascularized directly by the caudal mesenteric artery and that it arises inferior to the left renal artery. This conformation of the arteries and their irrigation is similar to those found in C. didactylus and B. variegatus by Alcântara et al (2020).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Souza et al (2010) found that the large intestine (colon and rectum) of the giant anteater ( Myrmecophaga tridactyla ) is vascularized directly by the caudal mesenteric artery and that it arises inferior to the left renal artery. This conformation of the arteries and their irrigation is similar to those found in C. didactylus and B. variegatus by Alcântara et al (2020).…”
Section: Discussionsupporting
confidence: 89%
“…As in other xenarthers (Alcântara et al, 2020;Carvalho et al, 2014;Ferreira et al, 2013;Souza et al, 2010), C. didactylus presents anatomical variations in the abdominal aorta, which directly implies interventions clinical and surgical, since the veterinarian can find peculiarities when performing procedures in the species of this group.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation